Advances in Mass Spectrometry for the Screening and Validation of Colorectal Cancer Biomarkers: A Review - Shi, Ruiyang (Exploring Science Academic Conference Series, 2026)
Colorectal cancer is a malignant tumor with persistently high incidence and mortality rates around the world. Early detection of colorectal cancer is essential to improving survival, yet current diagnostic tools show limited performance. Traditional screen ing methods, such as fecal occult blood testing, serum biomarker detection, and colonoscopy, have limitations in sensitivity, specificity, or patient compliance, making it difficult to meet the demands of large-scale early screening. Colorectal cancer, due to its high throughput and high sensitivity, enables the acquisition of much information in a single analysis, offering a new technological approach for the screening and validation of colorectal cancer biomarkers. The text systematically reviews the research progress on colorectal cancer markers based on mass spectrometric techniques. It concludes that the markers with potential research value in current studies include ROBO4, VCAM -1, phenylalanine, indoline, L -carnitine, and PSMD7. Although existing studies have demonstrated the great potential of mass spectrometry for marker discovery, most candidate markers remain in the exploratory stage, facing challenges such as small sample sizes, limited multicenter validation, and non -standardized detection workflows. In the future, the integration of mass spectrometry with multi -omics analysis is expected to advance colorectal cancer markers from research to clinical translation, enabling truly noninvasive early screening.